تقييم الأوضاع العامة في مصر من ثورة يناير حتى انتخابات 2018 - الكرد، دانا (المركز العربي للأبحاث ودراسة السياسات, 2018)
تعرض الورقة اتجاهات الرأي العام المصري تجاه الظروف السياسية والأمنية من كانون الثاني/ يناير 2011 إلى الانتخابات الرئاسية 2018. وتراجع الورقة آراء المواطنين المصريين حول الأحزاب السياسية والحكومة والانتخابات والمشاركة السياسية في العام الحالي والأعوام الماضية، كما تبحث في تأثير المخاوف الأمنية، وتزايد الرغبة في الاستقرار.
This paper presents an overview of evolving trends in Egyptian public opinion towards a host of security-related and political issues during the period between January 2011 and the 2018 presidential elections. The paper further provides an overview of Egyptians’ views of the political parties in their country; of their government; and of elections and political participation. Finally, the paper explores the impact of security concerns on Egyptian public attitudes and the increasing importance of the desire for stability in shaping public opinion in Egypt.
Keywords: مصر -- الربيع العربي -- ثورة 25 يناير 2011 -- المشاركة السياسية -- الانتخابات